"Rio Algom Investigations Into Preconcentration Of Uranium Ore" - M. E. Grimes (Society for Mining, Metallurgy & Exploration, 1973)
Rio Algom Mines Ltd. owns eight uranium mines and mills in the Elliot Lake district of Ontario, seven of which were producing before 1960. At present only one mine is operating meeting current contract requirements. Under present economic conditions, it is not feasible to mine ore of less than 2.0 lbs./ton U308, although there are very large reserves below this grade. We are interested in preconcentration for three possible applications: to extend ore reserves by permitting use of lower grade ore, to reduce costs on processing of present grade ore, and to reduce capital investment in expanding production to meet future production goals.